Polar protein Wag31 both activates and inhibits cell wall metabolism at the poles and septum - Habibi Arejan, Neda; Ensinck, Delfina; Diacovich, Lautaro; Patel, Parthvi Bharatkumar; Quintanilla, Samantha Y.; Emami Saleh, Arash; Gramajo, Hugo; Boutte, Cara C. (Frontiers in Microbiology, 2023)
Mycobacterial cell elongation occurs at the cell poles; however, it is not clear how cell wall insertion is restricted to the pole or how it is organized. Wag31 is a pole-localized cytoplasmic protein that is essential for polar growth, but its molecular function has not been described. In this study we used alanine scanning mutagenesis to identify Wag31 residues involved in cell morphogenesis. Our data show that Wag31 helps to control proper septation as well as new and old pole elongation. We have identified key amino acid residues involved in these essential functions. Enzyme assays revealed that Wag31 interacts with lipid metabolism by modulating acyl-CoA carboxylase (ACCase) activity. We show that Wag31 does not control polar growth by regulating the localization of cell wall precursor enzymes to the Intracellular Membrane Domain, and we also demonstrate that phosphorylation of Wag31 does not substantively regulate peptidoglycan metabolism. This work establishes new regulatory functions of Wag31 in the mycobacterial cell cycle and clarifies the need for new molecular models of Wag31 function.